Leukoencephalopathy After Excessive Cannabinoid Use - Korkmaz, Sevda; Gülşen, Sinem Çeçen; Tatlı, Sinan; Aytaç, Emrah; Kılıç, Nilüfer; Kaya, Şüheda (Physicians Postgraduate Press Inc., 2023)
[Abstract Not Available]
Keywords: Cannabinoids; Humans; Leukoencephalopathies; cannabinoid; cyanocobalamin; prednisolone; adult; anamnesis; blurred vision; body temperature; case report; clinical article; Cmt 1 gene; demyelinating disease; dysarthria; education; electromyography; emergency ward; gene; hereditary motor sensory neuropathy; human; leukoencephalopathy; male; neurologic examination; Note; paresthesia; psychiatrist; skin tingling; smoking; syphilis; urinalysis; young adult; leukoencephalopathy